PERTUMBUHAN EKONOMI PADA SEKTOR PARIWISATA HALAL DI INDONESIA - Indra Rizki Hasibuan; Anggi Nurul Assyfa Lubis; Anggara Rifandi; Dini Vientiany (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this review is to determine the impact of the halal tourism sector on economic growth, especially in the context of government policy. Halal tourism that follows Islamic Sharia principles is an important trend in global economic development. With the increasing number of Muslim tourists in various countries, the introduction of halal tourism can increase the country's competitiveness. Halal tourism has become the main focus of developing the tourism sector in Indonesia, with around 20 of the 15 million tourists visiting each year being Muslim tourists. Halal tourism has also become a public diplomacy tool for several countries, such as Japan, which has adopted a halal tourism policy as part of its country branding and soft power strategy. In terms of economic growth, the halal tourism sector is expected to make a positive contribution to the country's economic development. Therefore, this research investigates the impact of the halal tourism sector on economic growth, considering the role of government policy in developing the halal tourism sector. Through this study, it is hoped that we can find empirical evidence that the halal tourism sector has a positive impact on economic growth and provide policy recommendations to the government to encourage the halal tourism sector that supports sustainable economic growth.